Peningkatan Pemahaman mengenai Perencanaan Pensiun pada Guru SMK di Palembang - Fida Muthia; Agil Novriansa; Ichsan Hamidi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
One of the reasons for the emergence of the sandwich generation is the inability of parents to plan for retirement. One of the ways to break the sandwich generation chain is to do good financial management and planning. Good financial planning usually needs to be supported by a good level of financial literacy. One reason for the lack of knowledge in retirement planning is the low level of financial literacy in society. Therefore, it needs efforts to increase retirement planning knowledge to reduce the number of sandwich generation in Indonesia. The purpose of this service activity is to increase financial literacy in teachers and introduce retirement planning. The implementation of this community service activity is carried out using the lecture and discussion method. Activities are carried out in the form of webinars using the Zoom application. From the results of these community service activities, it can be assumed that there are still many teachers who do not realize the importance of preparing for pension funds. This is due to a lack of understanding of retirement planning.